A model of kin selection for an altruistic trait considered as a quantitative character. - Yokoyama, S (1978)
Conditions for natural selection to favor increase of a quantitative character are derived for a model in which individuals associate in groups of size n. It is assumed that the logarithm of the fitness of an individual is the sum of two parts, one proportional to the individual's own phenotype, and the other to the mean phenotype in its group. The resulting conditions for the trait to increase under natural selection are analogous to the results found previously in single-locus kin selection models.